A Structural Relationship of Change Management and its Supply Change Strategy for Improving Officer and Organizational Performance - Norma Yunita; Nasir Nasir; Muhammad Adam; Nudasila Darsono (International Journal of Supply Chain Management, 2020)
Nowadays, most institutions are working in an ever-changing, volatile, challenging, and competitive environment. It requires organizations to select the change in management strategies. Of these, the present study is written to examine the relationship of planned change, organizational climate and transformational leadership toward personnel performance and to determine the moderating role of bureaucratic reform in their relationship on institution performance. This study was designed using a quantitative approach through a survey questionnaire (self-administered). A total of 389 police personnel participated in this study. The data analyzed using the Structural Equation Modelling (SEM), by involving the Confirmatory Factor Analysis (CFA). Applying the SEM approach, this study found that the variable of planned change, organizational climate, and transformational leadership has a significant relationship toward personnel and institution performance. Also, personnel performance plays a role as a mediator variable to institution performance. Besides, this study also found that bureaucratic reform plays a role of moderating variable.Keywords—.Change Management; Supply Change Strategy, Organizational Performance; Officer Performance; Bureaucratic Reform